High-performance work systems in foreign subsidiaries of American multinationals: An institutional model - Lawler, John J; Chen, Shyh-jer; Wu, Pei-Chuan; Bae, Johngseok; Bai, Bing (Journal of International Business Studies, 2011)
This study examines the implementation of high-performance work systems (HPWSs) in 217 subsidiaries of American-based multinational enterprises operating in 14 countries in Asia, Africa, and Europe. Specifically, this paper explores the effect of host-country institutional factors on the extent of HPWS implementation in subsidiaries, and focuses on “strong agency” influences and dominance effects. The proposed model was more successful in explaining the effect of HPWSs on rank-and-file employees than on managers. Of particular interest is the strong positive association between host-country economic growth and HPWS implementation, which suggests a possible cyclical sensitivity of subsidiaries regarding human resource management strategy.